A Preliminary Study for Blended Learning Simulation Based Model on Aerodrome Flight Information Course - Rahayu Surtiningtyas, Sri (International Journal of Engineering and Technology, 2018)
The purpose of this study was to conduct preliminary study for an instructional model research and development which will be developed for Aerodrome Flight Information course in Indonesia Civil Aviation Institute. This preliminary study use step 3a blended learning decision matrix from Hew and Cheung 2014 that adapted from Foo 2014. The preliminary study was consisted systematic analysis of institutional support, infrastructure readiness, content readiness, instructor readiness, and student readiness. This preliminary research was carried out at Indonesia Civil Aviation Institute from February until April 2016. The data were collected through interview and field observation. The data analysis and interpretation indicates that (1) the briefing should be done instensively prior to role-play simulation, (2)according to time constraint, briefing should be held in online learning, (3)infrastucture, instructor, and learner suitable withÂ blended learning simulation based model. The finding lead to the recommendation to develop a blended-learning simulation based model for Aerodrome Flight Information course. The model should be developed in supplemental model which is retain face-to-face learning time and add some online learning activities.Â Â